2020
DOI: 10.3233/nre-203090
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of cognitive-cycling dual-task training in patients with early-stage Parkinson’s disease: A pilot study

Abstract: BACKGROUND: Recent studies have suggested that cognitive-motor dual-task (DT) training might improve gait performance, locomotion automaticity, balance, and cognition in patients with Parkinson’s disease (PD). OBJECTIVE: We aimed to investigate the efficacy of cognitive-cycling DT training in patients with early-stage PD. METHODS: Participants were scheduled to perform cognitive tasks simultaneously with the cycling training twice per week for eight weeks for a total of 16 sessions during their on-states. Clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 32 publications
0
10
1
Order By: Relevance
“…This means that those patients had participated in an intervention with a cycling protocol; however, they were assessed using a walking dual task and not a cycling dual task. Unlike in our pilot study, where we observed a deterioration of cycling performance, the aforementioned authors [30] observed improvements in different gait parameters while the cognitive task was being performed. It should be noted that, in our study, the different measurement tools were used at the beginning of the study and once again, seven weeks after the intervention had ended, except for the cycling performance parameters, which were collected at the same time as the cycling + cognitive task was performed.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…This means that those patients had participated in an intervention with a cycling protocol; however, they were assessed using a walking dual task and not a cycling dual task. Unlike in our pilot study, where we observed a deterioration of cycling performance, the aforementioned authors [30] observed improvements in different gait parameters while the cognitive task was being performed. It should be noted that, in our study, the different measurement tools were used at the beginning of the study and once again, seven weeks after the intervention had ended, except for the cycling performance parameters, which were collected at the same time as the cycling + cognitive task was performed.…”
Section: Discussioncontrasting
confidence: 82%
“…Regarding the development of the cycling task, the concomitance of the cognitive task generated a difficult element in its performance, although without generating, for example, changes in symmetry between hemi bodies or Heart Rate. In the study by Chang et al [30], gait parameters were evaluated while Parkinson's patients performed different cognitive tasks associated with walking; one of them related to calculations, another with spatial orientation and finally one was carried out using the STROOP test. In that study, the total cycling time was 30 min for five-eight sessions, 35 min for nine-twelve sessions, and 40 min for thirteen-sixteen sessions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that motor symptoms were improved after dual-task training [ 18 , 19 , 20 ]. Twenty patients were randomized into a 24-session single-modal training group (performing gait and cognitive training sequentially) or a dual-task training group (performing gait and cognitive training simultaneously).…”
Section: Effects Of Dual-task Training On Cognitive and Physical Func...mentioning
confidence: 99%
“…The improvement in motor symptoms could be preserved for at least 4 weeks [ 18 ]. Another study found that the shorter session of cognitive-cycling training (16 sessions) also showed benefits [ 20 ]. The Hoehn–Yahr stage of the included patients ranged from two to three, indicating that the dual-task training was suitable for mild to moderate PD [ 18 , 19 , 20 ].…”
Section: Effects Of Dual-task Training On Cognitive and Physical Func...mentioning
confidence: 99%
See 1 more Smart Citation